2022
DOI: 10.3390/diagnostics12020251
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of BTLA, CD27, CD70, CD28 and CD80 as Diagnostic and Prognostic Markers in Ovarian Cancer

Abstract: It is very important to find new diagnostic and prognostic biomarkers. A total of 79 patients were enrolled in the study. The study group consisted of 37 patients with epithelial ovarian cancer, and the control group consisted of 42 patients with benign ovarian lesions. Five proteins involved in the immune response were studied: BTLA, CD27, CD70, CD28, CD80. The study material was serum and peritoneal fluid. The ROC curve was plotted, and the area under the curve was calculated to characterize the sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…The older the age, the more gene accumulation (Franco et al, 2019;Szilard, 1959); therefore, it was speculated that age may increase the expression of BTLA by cumulative mutations, which promotes the occurrence and development of cancer. At present, the clinical research on BTLA is not sufficient, but only from the existing test, the separate expression of BTLA is associated with the prognosis of patients with nonsmall cell lung cancer (NSCLC) and OV (Li et al, 2020;Świderska et al, 2022), which is consistent with the results of BTLA pan-cancer prognosis analysis, reflecting the potential of BTLA as a prognostic marker for cancer patients to evaluate the survival status of patients. In these cancers, the expression of BTLA is often a poor prognostic factor, which is consistent with the biological characteristics of BTLA inhibiting lymphocytes and providing some evidence for the efficacy of immune-checkpoint inhibitors targeting BTLA.…”
Section: Discussionmentioning
confidence: 53%
“…The older the age, the more gene accumulation (Franco et al, 2019;Szilard, 1959); therefore, it was speculated that age may increase the expression of BTLA by cumulative mutations, which promotes the occurrence and development of cancer. At present, the clinical research on BTLA is not sufficient, but only from the existing test, the separate expression of BTLA is associated with the prognosis of patients with nonsmall cell lung cancer (NSCLC) and OV (Li et al, 2020;Świderska et al, 2022), which is consistent with the results of BTLA pan-cancer prognosis analysis, reflecting the potential of BTLA as a prognostic marker for cancer patients to evaluate the survival status of patients. In these cancers, the expression of BTLA is often a poor prognostic factor, which is consistent with the biological characteristics of BTLA inhibiting lymphocytes and providing some evidence for the efficacy of immune-checkpoint inhibitors targeting BTLA.…”
Section: Discussionmentioning
confidence: 53%
“…The interaction of CD70 with its receptor, CD27, results in B- and T-cell activation. In a recent study, Swiderska et al found evidence of a correlation between the serum CD70 concentration and overall survival in patients with ovarian cancer [ 17 ]. The authors also showed that higher concentrations of CD70 in the peritoneal fluid were associated with peritoneal carcinomatosis.…”
Section: Discussionmentioning
confidence: 99%
“…BTLA levels in tumor tissue have been linked to poor prognoses for ovarian and breast cancer patients. Another study [15], found that ovarian cancer patients had significantly higher median protein concentrations (BTLA, CD27, CD28, and CD80) in their blood. Recent research linked BTLA to lower immune checkpoint inhibitor patient survival.…”
Section: Investigating the Correlation Of Patient's Serum Levels Usin...mentioning
confidence: 96%